CAUSES OF UNEMPLOYMENT IN UZBEKISTAN - Mamajonov Raximjon Akramovich (TADQIQOTLAR.UZ, 2023)
Abstract : This article describes the causes of unemployment and the problems arising in ensuring employment in Uzbekistan and the results of the work being done to eliminate them. The article also contains the scientific proposal and practical recommendations made by the author on this issue.